Determinant of Foreign Direct Investment in Indonesia Plantation Sector - RIZKY P. LUBIS; MUHAMMAD FIRDAUS; HENDRO SASONGKO (Jurnal Bisnis Manajemen, 2015)
Realization of investment in Indonesia is dominated by foreign investors where capital intensive sector such as mining industry is the primary focus. To strengthen their roles in national economies, foreign investors should be directed to plantation sector since it has huge role in labor absorption and positive trade balance. According to MP3EI, realization of investment in plantation sector has reached 2.29 percent in march 2013 which was still below of target. This research aimed to analyze determinants of foreign direct investment conducted vector error correction model analysis and formulated strategies by using SWOT matrix to increase Indonesia plantation sector. Variables used in this model were foreign direct investment, exports value, exchange rates, domestic interest rates, interest rates in United State of America, consumer price index, gross domestic product and crisis as dummy variable. The strategy alternatives were formulated by SWOT model based on the questionnaire and respondents interview designed in analytical hierarchy process framework. The result from model suggested that in the short term exchange rate, value of exports, United States interest rates, gross domestic product and consumer price index had positive impact to foreign direct investment. On the other side crisis had negative impact. Meanwhile in long term, domestic interest rates, gross domestic product and consumer price index had positive impact but crisis had negative contribution. The strategy priority to increase foreign direct investment in Indoensia plantation sector can be undertaken through harmonization between central and local governments regulations.Keywords: Foreign Direct Investment, Vector Error Correction Model, SWOT Matrix